Exosomal 2′, 3′-CNP from mesenchymal stem cells promotes hippocampus CA1 neurogenesis/neuritogenesis and contributes to rescue of cognition/learning deficiencies of damaged brain. (15th January 2020) - Chen, Shih-Yin; Lin, Meng-chieh; Tsai, Jia-Shiuan; He, Pei-Lin; Luo, Wen-Ting; Chiu, Ing-Ming; Herschman, Harvey R.; Li, Hua-Jung
Abstract: Mesenchymal stem cells (MSCs) have been used in clinical studies to treat neurological diseases and damage. However, implanted MSCs do not achieve their regenerative effects by differentiating into and replacing neural cells. Instead, MSC secretome components mediate the regenerative effects of MSCs. MSC-derived extracellular vesicles (EVs)/exosomes carry cargo responsible for rescuing brain damage. We previously showed that EP4 antagonist-induced MSC EVs/exosomes have enhanced regenerative potential to rescue hippocampal damage, compared with EVs/exosomes from untreated MSCs. Here we show that EP4 antagonist-induced MSC EVs/exosomes promote neurosphere formation in vitro and increase neurogenesis and neuritogenesis in damaged hippocampi; basal MSC EVs/exosomes do not contribute to these regenerative effects. 2′, 3′-Cyclic nucleotide 3′-phosphodiesterase (CNP) levels in EP4 antagonist-induced MSC EVs/exosomes are 20-fold higher than CNP levels in basal MSC EVs/exosomes. Decreasing elevated exosomal CNP levels in EP4 antagonist-induced MSC EVs/exosomes reduced the efficacy of these EVs/exosomes in promoting β3-tubulin polymerization and in converting toxic 2′, 3′-cAMP into neuroprotective adenosine. CNP-depleted EP4 antagonist-induced MSC EVs/exosomes lost the ability to promote neurogenesis and neuritogenesis in damaged hippocampi. Systemic administration of EV/exosomes from EP4 -antagonist derived MSC EVs/exosomes repaired cognition, learning, and memory deficiencies in mice caused by hippocampal damage. In contrast, CNP-depleted EP4 antagonist-induced MSC EVs/exosomes failed to repair this damage. Exosomal CNP contributes to the ability of EP4 antagonist-elicited MSC EVs/exosomes to promote neurogenesis and neuritogenesis in damaged hippocampi and recovery of cognition, memory, and learning. This experimental approach should be generally applicable to identifying the role of EV/exosomal components in eliciting a variety of biological responses. : Abstract : EP4 antagonist-induced mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs)/exosomes contain elevated cyclic nucleotide 3′-phosphodiesterase (CNP). Exosomal CNP contributes to the ability of EP4 antagonist-elicited MSC EVs/exosomes to rescue cognition/learning deficiencies of damaged brain. Decreasing exosomal CNP levels in EP4 antagonist-induced MSC EVs/exosomes reduced the efficacy of these EVs/exosomes in promoting β3-tubulin polymerization, in converting toxic 2′, 3′-cAMP into neuroprotective adenosine, and in promoting neurogenesis and neuritogenesis. Scale bars, 50 μm. ** P ≤ .005.